Pengaruh Gaya Hidup dan Aksesibilitas Terhadap Keputusan Pembelian Menggunakan Shopee Paylater: Studi pada Perilaku Keuangan Remaja Usia 17-25 Tahun (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of lifestyle and accessibility on purchasing decisions using the Shopee PayLater feature among adolescents aged 17–25. Employing a quantitative approach and multiple linear regression analysis on 73 respondents, the results show that both lifestyle and accessibility have a positive and significant effect on purchasing decisions, both simultaneously and partially. The coefficient of determination (R²) of 79.3% indicates that these variables explain most of the variation in purchasing decisions. A consumptive lifestyle and ease of access are proven to drive adolescent purchasing behavior through digital credit services.